Solid state fermentation as a method to reduce anti-nutritional factors in the flour of Artocarpus altilis fruits - Brea Maure, Odelín; Borrás Sandoval, Luis Miguel; Rache Cardenal, Leidy Yanira (Universidad Pedagógica y Tecnológica de Colombia, 2022)
With solid-state fermentation, complex organic substances are used in simple ones by the action of microbial enzymes and the physical chemical characteristics of the food are modified, leading to an improvement in the bioavailability and quality of the nutrients when different plant species are used as animal feed. Secondary metabolites produced by plants can affect the health of animals when they consume them. Eliminating or reducing the quantity of harmful compounds, in addition to improving the nutritional value, is a priority. In the present work, solid state fermentation with some modifications is evaluated as an option to eliminate or reduce the content of tannins and saponins present in the flour of the fruit of Artocarpus altilis (breadfruit). The effect of fermentation time, the addition of urea, vitafer and calcium carbonate at different concentrations was analyzed. The results of the phytochemical screening and the quantification of tannins and saponins in the different fermentation variations show that adding Vitafer (5%) and calcium carbonate (0.6%) decreases the concentration of tannins and saponins in the flour of the fruit of Artocarpus altilis.